Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1096/fasebj.22.1_supplement.971.12
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological characteristics of freshly isolated ventricular myocytes from Zebrafish (Danio rerio)

Abstract: The Zebrafish (ZF) is a tropical fish that has been the focus of an increasing number of developmental studies. However, our understanding of the basic physiology of ZF, in particular cardiac excitation‐contraction coupling is limited. Indeed, there is currently no information about the electrical activity of single myocytes freshly isolated from ZF ventricle; this study addressed this point. Ventricular myocytes were obtained by enzymatic digestion. The patch clamp technique was used to record Na currents (IN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, while Ca 2+handling mechanisms are also generally well conserved between zebrafish and humans (Rayani et al, 2018;van Opbergen, et al, 2018), aspects of excitation-contraction coupling do appear to differ. Zebrafish cardiomyocytes may be more dependent on extracellular Ca 2+ influx (including through T-type Ca 2+ channels) than intracellular sarcoplasmic reticulum Ca 2+ release for contraction, due to the apparent low Ca 2+ sensitivity of their ryanodine receptors (Bovo et al, 2013) and paucity of transverse tubules (Brette et al, 2008) (although others have shown a strong dependence of contractile force on the release of Ca 2+ from the sarcoplasmic reticulum (Haustein et al, 2015). Zebrafish also have a higher sodium-Ca 2+ exchanger current than in mammals, such that its reverse-mode has been shown to trigger sarcoplasmic reticulum Ca 2+ release (Zhang et al, 2011).…”
Section: Zebrafish As An Experimental Model For the Study Of Cardiac ...mentioning
confidence: 99%
“…However, while Ca 2+handling mechanisms are also generally well conserved between zebrafish and humans (Rayani et al, 2018;van Opbergen, et al, 2018), aspects of excitation-contraction coupling do appear to differ. Zebrafish cardiomyocytes may be more dependent on extracellular Ca 2+ influx (including through T-type Ca 2+ channels) than intracellular sarcoplasmic reticulum Ca 2+ release for contraction, due to the apparent low Ca 2+ sensitivity of their ryanodine receptors (Bovo et al, 2013) and paucity of transverse tubules (Brette et al, 2008) (although others have shown a strong dependence of contractile force on the release of Ca 2+ from the sarcoplasmic reticulum (Haustein et al, 2015). Zebrafish also have a higher sodium-Ca 2+ exchanger current than in mammals, such that its reverse-mode has been shown to trigger sarcoplasmic reticulum Ca 2+ release (Zhang et al, 2011).…”
Section: Zebrafish As An Experimental Model For the Study Of Cardiac ...mentioning
confidence: 99%